2004
DOI: 10.1117/12.540002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SMA hybrid composite structures using commercial codes

Abstract: A thermomechanical model for shape memory alloy (SMA) actuators and SMA hybrid composite (SMAHC) structures has been recently implemented in the commercial finite element codes MSC.Nastran and ABAQUS. The model may be easily implemented in any code that has the capability for analysis of laminated composite structures with temperature dependent material properties. The model is also relatively easy to use and requires input of only fundamental engineering properties. A brief description of the model is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…For easy comparison the beam specimen considered here is same as the one used by Turner and Patel [33] with slight modifications in the finite element model and mesh to render it suitable for analysis with the 1D SMA user element. The experimental beam specimen is 18 inches long (45.72 cm) and 1 inch wide (2.54 cm) and clamped at both ends.…”
Section: Clamped Sma Hybrid Composite Beammentioning
confidence: 99%
See 1 more Smart Citation
“…For easy comparison the beam specimen considered here is same as the one used by Turner and Patel [33] with slight modifications in the finite element model and mesh to render it suitable for analysis with the 1D SMA user element. The experimental beam specimen is 18 inches long (45.72 cm) and 1 inch wide (2.54 cm) and clamped at both ends.…”
Section: Clamped Sma Hybrid Composite Beammentioning
confidence: 99%
“…Extensive experimental and modeling work has also been conducted on active SMA polymer composites by Turner and his collaborators at NASA Langley Research Center [28][29][30][31][32][33]. Figure 1 shows a conceptual airplane with morphing airfoil made of shape memory alloy hybrid composite and the adaptive stiffening prototype beam at NASA undergoing a temperature ramp test.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used as "smart" components embedded into the conventional resins or composites so as to obtain active abilities, including in tunable stiffness, damping capacity, shape-controllable active surfaces and self-healing capability. Many works have been done and shown that SMAs have significant potential applications for vibration control and structural control [2][3][4][5][6][7][8]. Although two-dimension weaving metal wires, such as stainless wires, are common in industry applications, to the authors' knowledge, a preliminary study of weaving SMA wires has been reported by Boussu et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results will be limited to ABAQUS in the present study. Additional detail about the constitutive model and its implementation in the commercial codes can be found elsewhere [9][10] .…”
Section: Numerical Modelingmentioning
confidence: 99%